BUPROPION FOR ADHD: MECHANISMS OF ACTION AND ITS POTENTIAL AS AN ALTERNATIVE TREATMENT — A REVIEW - Martyna Narożniak; Bartłomiej Czerwiec; Julia Skowrońska-Borsuk; Adam Borsuk; Joanna Pergoł; Malwina Wojtas; Adrianna Ewa Pękacka; Julia Borkowska; Zuzanna Krupa; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common psychiatric disorders in childhood. Its core symptoms are related to executive dysfunction and include inattention, hyperactivity, and impulsivity. As a neurodevelopmental disorder, ADHD requires chronic, long-term treatment. Therefore, it is essential to identify the most effective and safest therapeutic options that minimize the side effects of prolonged pharmacological intervention.Aim of the Study: This article examines the potential role of bupropion in ADHD treatment, focusing on its mechanism of action, efficacy in symptom alleviation, and possible side effects.Materials and Methods: This review was conducted using multiple databases, including PubMed, Scopus, and Google Scholar. The search terms used were: “ADHD”, “bupropion”, “methylphenidate”, “comorbidity”, “side effects”, and “non-stimulants”.Summary of Current Knowledge: ADHD should be managed with both pharmacological and non-pharmacological methods. While methylphenidate is considered first-line pharmacological treatment, it is associated with a relatively high discontinuation rate. Bupropion, as an alternative, may offer effective symptom relief and better tolerability in patients who experience severe side effects from stimulant medications.Conclusions: Bupropion appears to be effective in treating ADHD compared to placebo and is generally well tolerated, especially in contrast to first-line stimulant treatments. It may be a viable alternative for patients who do not tolerate stimulants. However, further research using objective comparative methods is necessary to evaluate the effectiveness and side effect profiles of bupropion versus methylphenidate.